FINANCIAL DISTRESS AND MANAGERIAL ABILITY ON AUDIT FEE - Lauwangsa, Jovan Krishna; Suryadi, Vanya Amartyazenna; Adelina, Yang Elvi; Gunawan, Vania Pradipta (Jurnal Akuntansi Kontemporer, 2023)
Research Purposes. This paper examines the effect of managerial ability on audit fees, examines the effect of financial difficulties on the relationship between managerial ability and audit fees, and examines the effect of opportunistic reporting carried out by management in the form of earning management on audit fees. Research Method. The studies that were carried out used secondary data from 139 non-financial companies listed on the Indonesia Stock Exchange from 2016 to 2020. Research Result and Findings. Through a linear regression of panel data, the study found that higher amount of audit fees was positively influenced by the manager's ability to manage company resources and found that abnormal cash flow real earning management had a positive influence on audit fees. The study also found that financial difficulties did not moderate the relationship between a company's managerial ability and its audit fees, but found that companies with financial difficulties had higher audit fees.